RESPON KELUARGA PENERIMA MANFAAT PROGRAM KELUARGA HARAPAN TERHADAP PROGRAM GRADUASI MANDIRI DI KELURAHAN KARANGMEKAR KECAMATAN CIMAHI TENGAH KOTA CIMAHI - Herdiawan Gumbira; Raden Enkeu Agiati; Bambang Indrakentjana (Jurnal Ilmiah Rehabilitasi Sosial (Rehsos), 2022)
Responses of Beneficiary Families of the Family Hope Program to the Independent Graduation Program refer to answers, replies orreactionsto questions about graduation. This study aims to obtain an empirical description of: 1) respondents' characteristics, 2) cognitive responses of respondents, 3) affective responses of respondents, 4) behavioral responses of respondents to the Independent Graduation Program, and 5) respondents' constraints in doing independent graduation, The method used in this research is quantitative research with descriptive method. Sources of data used are primary and secondary data sources. The population in this study is the Beneficiary Families of the Family Hope Program (PKH) who have had Independent Graduation. The sampling technique in this research is cluster random sampling. The data collection techniques used are: 1) questionnaire, 2) observation, and 3) documentation study. The measuring instrument uses a rating scale. Test face validity and reliability using Cronbach's Alpha. The results showed that the response of KPM PKH to the Graduation Program was high. However, the response aspect has the lowest score. Therefore, it is proposed the program "Assistance to Beneficiary Families of the Hopeful Family Program in Graduation" in Karangmekar Village, Central Cimahi District, Cimahi City.